Characterizing global gene expression and antiviral response in Frankliniella occidentalis infected with Tomato spotted wilt virus - Schneweis, Derek Joseph (Kansas State University, 2017)
Frankliniella occidentalis, the western flower thrips, transmits the plant-pathogenic virus, Tomato spotted wilt virus (TSWV), through a circulative-propagative transmission strategy. The virus infects and replicates in the insect, traversing membrane barriers as it moves from the midgut to the salivary glands for subsequent inoculation of a plant host. Based on well-characterized virus-vector systems, many molecular interactions occur as the virus completes an infection cycle in the vector, and knowledge of transcriptome-wide response of thrips to TSWV has been limited. My research goals were to gain insight into i) the molecular responses that occur in thrips vectors of orthotospoviruses, ii) the role of antiviral defense in viruliferous thrips, and iii) plant transgenic-based strategies for studying thrips gene function and crop-pest control. To this end, my specific research objectives were to: 1) generate, assemble, and annotate a RNA-Seq-derived transcriptome for F. occidentalis using the thrips genome, and to quantify global gene expression in response to TSWV activity in larval, pre-pupal, and adult developmental stages, 2) conduct a time-course experiment to determine the effect(s) of challenging TSWV-exposed and non-exposed thrips with dsRNAs of F. occidentalis Dcr-2 or AGO2 by hemocoel injection, and 3) construct transgenic plants expressing a thrips-gene specific dsRNA hairpin to target a vital gene. My research has catalogued insect response to TSWV activity in thrips during development and provides candidate sequences for functional analysis of genes involved in insect development and defense. Successful silencing of the antiviral RNAi pathway in thrips revealed increased mortality and decreased offspring production in both virus-exposed and non-exposed insects. Arabidopsis plants were developed to express dsRNA of vacuolar ATP synthase (V-ATPase) and preliminary feeding bioassays to explore the effect of these transgenics on thrips fitness indicate a need for further description of thrips dsRNA uptake. In total, my research contributes new basic knowledge underpinning the complex and dynamic relationship between thrips vectors and the plant viruses they transmit.
Keywords: Bunyaviridae; Thysanoptera; Tospovirus; Virus-vector interactions; Western flower thrips; Transcriptome